Improving the Function of the Supreme Court Research and Development Center: Implementation of QSPM and SWOT - Alfi Syahr, Zulfia Hanum (Jurnal Bina Praja, 2018)
Research and development center (here refers to as Puslitbang) of the Supreme Court has an important role in the development process of law and justice in Indonesia. Puslitbang must be able to support the Supreme Court’s vision to create a great judicial firm. However, activities of Puslitbang of the Supreme Court are still limited to the implementation of research and review of certain topics. Whereas, Puslitbang has so many assignments beside doing research and review, which is described in Chief of the Supreme Court Decree Number: 140/KMA, SK/X/2008 on Guidance for Management and Implementation of Research, Development, Education, and Training. The other assignment of Puslitbang include: feasibility of the policy plan and carry out activities in developing models/legal and judicial products. So, it can be said that Puslitbang has not performed its full functions as described in Chief of the Supreme Court Decree Number: 140/KMA, SK/X/2008. The purpose of this study is to determine the strategy to improve the functions of Puslitbang of Supreme Court. This paper used descriptive-quantitative research with Quantitative Strategic Planning Matrix (QSPM) method. The first step of this method is determining the internal and external factors affecting the management of Puslitbang and then analyzing them using SWOT and QSPM. The results show that the strategy that obtains the highest score is organizing discussion forums with external and internal institutions. On the other hand, the strategy which obtains the lowest score is the leader’s role in determining policy by considering the needs of Puslitbang. The conclusion of this research is the QSPM method provides 4 best strategies for enhancing the function of Puslitbang. The strategies are: creating a discussion forum with internal and external institutions, budget flexibility, developing Puslitbang Human Resources, and preparing activities in accordance with the capacity of puslitbang resources.